FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY PADA PERUSAHAAN DAGANG DI BURSA EFEK INDONESIA - Sulistiyanto, Andi; Yuniarto, Arif Sapta (Universitas Ahmad Dahlan, 2012)
Time difference between financial statement and auditing opinion date indicates the amount of time needed in auditing settlement period. This condition can affect the punctuation of the information published and will inflence market reaction towards the lengthy information. It will also the level of uncertainly based on the published information in the auditor’s financial. Statement in which containing company’s profit information. This study aims to measure the factors which affect audit delay. They are profitability, company size, and the size of the public accountant. The population of the study is the trading companies registered in Indonesian Stock Exchange in the period 2006-2010. Sampling technique employed in this study is the purposive sampling with the total sample of 23 companies. The result of the study shows that the profitability, company size, and the size of the public accountant have significant influence towards audit delay.